(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the issues of regional integration in the Uzbek-Kazakh relations in the years of independence. It discusses the efforts of the two countries in this direction, the problems that have arisen, the intervention of external forces, the collapse of Central Asian integration and the role of the leaders of the two countries in the integration process. Particular attention is also paid to the approaches of both countries to regional integration.